Use of diverging apertures to minimize the edge scatter in passive scattering proton therapy. (8th September 2015) - Zhao, Tianyu; Cai, Bin; Sun, Baozhou; Grantham, Kevin; Mutic, Sasa; Klein, Eric
Abstract : The purpose of this study was to evaluate the use of diverging‐cut aperture to minimize collimator contamination in proton therapy. Two sets of apertures with nondivergent and divergent edge were fabricated to produce a 10   cm × 10   cm field at the radiation isocenter of a single‐room proton therapy unit. Transverse profiles were acquired in a scanning water tank with both aperture sets. Up to 9.5% extra dose was observed from aperture scattering near the field edges with the nondivergent aperture set at 2 cm above the water surface and remained 3.0% at depth of 10 cm. For the divergent set, the contamination was reduced to less than 3.5% and 1.3%, respectively. Our study demonstrated that scattering from apertures contaminated the dose distribution near the field edge at shallow depth. A diverging‐cut aperture was capable of reducing the contamination and is recommended for use in passive scattering proton therapy, especially when critical organs are lateral and proximal to the target at shallow depth. PACS numbers: 87.55.ne, 87.56.nk